Laser crown lengthening and direct composite veneers as single-visit treatment - Dr Jovan Cabunac; A/Prof Tatjana Savic-Stankovic; Prof Vesna Miletic (Elsevier, 2023)
Introduction: Minimally invasive treatment of gummy smile is essential when there is additional need for veneer restorations. This case report presents long-term treatment results of single-visit treatment of three patients with laser-corrected gummy smile and direct composite veneers. Case Description: : Three patients presented with moderate to pronounced gummy smile and unremarkable medical/medication history. Direct veneers were indicated to manage anterior diastemas, caries or failing restorations. Crown lengthening was performed with Er,Cr:YSGG laser (Waterlase MD, Biolase). Teeth were isolated, adhesive (G Bond, GC) was applied following a total-etch technique, followed by a thin layer of flowable composite (Gradia Direct Flo, GC) in the demarcation zone and uniersal composite (Gradia Direct, GC). Postoperatively, there was no bleeding, swelling or pain. Gingival inflammation subsided after 6 days.Long-term follow-up showed stable position of gingival margin without recession up to 15 years postoperatively. Composite veneers required repolishing or superficial repair to maintain superior aesthetics but without complete replacement. Discussion: No data exists on long-term outcomes of laser-corrected gummy smile with direct composite veneers in the same visit. This case series shows no postoperative complications and stable periodontal results achieved with laser crown-lengthening for up to 15 years. Flowable composite was used to allow precise and pressure-free adaptation, minimizing the risk of trauma of laser-treated gingiva. Dentine and enamel shades of the sculptable composite allowed highly aesthetic shade matching. Conclusion: Crown lengthening using Er,Cr:YSGG laser and direct composite veneers are minimally invasive surgical and restorative treatment options, respectively, to correct gummy smile and manage caries, failing restorations and/or inadequate tooth position/size/shape in the same visit.